O Programa Institucional de Bolsa de Iniciação a Docência e as repercussões nas práticas pedagógicas desenvolvidas pelos egressos do subprojeto Pedagogia/PIBID/UFSM - Zwetsch, Andriele dos Santos (2021)
This study presents the dissertation linked to the Graduate Program in Education (PPGE), in the LP2 research line entitled: “Educational public policies, educational practices and their interfaces”, and to the Elos Research Group, from the Federal University of Santa Maria (UFSM). As a research issue, the question is: "What are the repercussions that the PIBID provided for the pedagogical practices developed in the school context, considering the scholarship holders graduated from the Pedagogy/PIBID/UFSM Subproject, who are in the teaching practice?". Furthermore, it aims to understand the repercussions of PIBID for pedagogical practices developed in the school context by active teachers, who are scholarship holders from the Pedagogy/PIBID/UFSM Subproject. The methodology was based on a qualitative approach, of the case study type. The data were built based on a literature review, document analysis and through questionnaires with open questions, having as research subjects the graduates of the Pedagogy/PIBID/UFSM Subproject from 2009 to 2019 who are in the teaching profession. It takes as reference the studies of: Libâneo (2010), Gatti (2010), Freire (1996), Becker (2012), Vieira (2007), Bolzan (2002), Dourado (2009), among other references studied. This research demonstrates the significant importance of PIBID, as a public policy for initial teacher education, for the training process and for the development of qualified pedagogical practices.